Homoeopathic Management of Duchenne Muscular Dystrophy: A Case Report - Sahoo, Sanjib; Bhattacharya, Soumya; Dutta, Abhijit (Homœopathic Links, 2022)
Background Duchenne muscular dystrophy (DMD) is a hereditary disorder having a significant socioeconomic burden. Primary abnormality may be in muscle membrane, due to the alterations of dystrophin protein. The patient usually has trouble in muscular activities like running, climbing staircases, jumping, getting up from the ground, suffers from frequent falls and gait abnormality. Owing to the limited therapeutic modality for DMD in conventional medicine, an alternative approach is warranted.Case Report An 8-year-old male child presented with unsteady gait, frequent falls, polymyalgia and weakness of limbs. Based on the clinical presentation and laboratory investigations, we diagnosed the case as DMD. On laboratory investigation, the serum creatine phosphokinase (CPK) level was significantly raised. After a thorough clinical evaluation, he was treated with Radium bromide, Veratrum viride and Calcarea phosphorica at different time points. Clinically, the improvement was marked in regard to symptomatology and reduced serum CPK level.Conclusion This is the first case demonstrating a favourable therapeutic course of homoeopathic treatment in DMD. For any further conclusion regarding the causal attribution, an individualistic n-of-1 trial may be warranted.
Keywords: Duchenne muscular dystrophy; homoeopathy; case report; n-of-1 trial